Ethylene Receptors in Nonplant Species. Issue 8 (28th July 2019) - Carlew, T. Scott; Allen, Cidney J.; Binder, Brad M.
Abstract: The effects of ethylene and ethylene signal transduction have been long studied in plants. It is only recently reported that a single‐celled cyanobacterium, Synechocystis, contains a functional ethylene receptor. However, it remains to be determined if functional ethylene receptors are more widespread. This review summarizes what is known about responses to ethylene, ethylene receptors, and signal transduction in nonplant species. A summary is provided of information gleaned from searches of sequenced genomes and the possibility that ethylene receptors are widespread in microbes is discussed. Abstract : The effects of ethylene and ethylene signal transduction are well studied in plants, but very little research has focused on ethylene in non‐plant species. This review summarizes what is known about responses to ethylene and ethylene signaling in non‐plant species. The possibility that ethylene receptors are wide‐spread in non‐plant species is discussed.